2017
DOI: 10.1093/database/baw168
|View full text |Cite
|
Sign up to set email alerts
|

KTCNlncDB—a first platform to investigate lncRNAs expressed in human keratoconus and non-keratoconus corneas

Abstract: Keratoconus (KTCN, OMIM 148300) is a degenerative eye disorder characterized by progressive stromal thinning that leads to a conical shape of the cornea, resulting in optical aberrations and even loss of visual function. The biochemical background of the disease is poorly understood, which motivated us to perform RNA-Seq experiment, aimed at better characterizing the KTCN transcriptome and identification of long non-coding RNAs (lncRNAs) that might be involved in KTCN etiology. The in silico functional studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…These results have shown that some of those non-coding RNAs could affect the expression of at least 996 genes in keratoconus patients ( Table 1 ) (compared to healthy subjects). The differentially regulated genes include very relevant cellular metabolism and fate regulators such as TGF-β and SMAD9, SMAD6, TGFB3, and TGFBR1 members of Hippo/Wnt pathways ( Szczesniak et al, 2017 ). All those have been previously associated with keeping ocular health ( Morgan et al, 2013 ).…”
Section: Ocular Surface Disordersmentioning
confidence: 99%
“…These results have shown that some of those non-coding RNAs could affect the expression of at least 996 genes in keratoconus patients ( Table 1 ) (compared to healthy subjects). The differentially regulated genes include very relevant cellular metabolism and fate regulators such as TGF-β and SMAD9, SMAD6, TGFB3, and TGFBR1 members of Hippo/Wnt pathways ( Szczesniak et al, 2017 ). All those have been previously associated with keeping ocular health ( Morgan et al, 2013 ).…”
Section: Ocular Surface Disordersmentioning
confidence: 99%
“…By 2005, differentially expressed proteins in KC patients have been investigated using either the whole cornea, certain layer, or tears [19][20][21][22] . In 2017, Szcześniak et al and Kabza M et al used RNA-Seq to determine differentially expressed RNAs between KC-affected and other disease affected corneas 23 .…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 By 2005, differentially expressed proteins in KC patients have been investigated using the whole cornea, certain layer, or tears. 22 25 In 2017, Szcześniak et al 26 and Kabza et al 27 used RNA-Seq to determine differentially expressed RNAs between KC-affected and other disease affected corneas.…”
mentioning
confidence: 99%